Investigation of DNA damage, oxidative stress, and inflammation in synthetic cannabinoid users - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2020)
Background: The widespread use of synthetic cannabinoids (SCs) among youth has become an important public health problem. Several life-threatening side effects of SC have been reported, including cardiovascular, gastrointestinal, neurological, renal, metabolic, ophthalmologic, and pulmonary effects, besides skin toxicity and hepatotoxicity. Methods: Given that high levels of SC can lead to oxidative stress, DNA damage, and inflammation, it has been aimed in this study to investigate the effects of SC in aspects of primary DNA damage, plasma total oxidant status (TOS)/total antioxidant status (TAS), thiol-disulfide homeostasis, myeloperoxidase (MPO) level, and cytokine levels (interleukin 1 beta (IL-1 beta), interleukin 6 (IL-6), and tumor necrosis factor-alpha (TNF-alpha)) of 40 SC users (SCUs) in Turkey. Results: Mean plasma TOS levels were significantly higher in the SCUs group than in the healthy group (HG). Similarly, mononuclear leukocyte DNA damage, plasma TOS, MPO activity, disulfide, oxidative stress index levels, IL-1 beta, IL-6, and TNF-alpha levels were significantly higher in the SCU group than in the HG, whereas plasma TAS, total, and native thiol levels were significantly lower in the SCU group than in the HG. Conclusion: It is concluded that SC can cause increase in oxidative stress and in inflammatory processes in addition to its potential for DNA damage. Additional studies with larger sample sizes and longer durations should be held to understand more specific outcomes of SC use.
Keywords: Synthetic cannabinoids; DNA damage; oxidative stress; inflammation; thiol-disulfide homeostasis; GENOTOXIC PROPERTIES; IN-VITRO; COMPLICATIONS; INHIBITION; MARIJUANA; ENZYMES; SYSTEM; CANCER; CELLS; ASSAY